Thermally conductive sheet, heat dissipation device, and method for manufacturing thermally conductive sheet

By using graphite particles and low melting point metal components in the thermal conductor sheet, the low thermal resistance and high adhesion of the thermal conductor sheet are achieved, the problem of increasing thermal resistance in semiconductor packaging is solved, and the need for high-density heating is adapted.

CN119137735APending Publication Date: 2024-12-13RESONAC CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380037697.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-22
Filing Date
2023-07-21
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

When existing heat conductors cope with the increase in heat generation caused by the semiconductor's performance and scale-up, it is difficult to effectively reduce thermal resistance, especially when the chips are crimpeded with different heights, the thermal conductivity is insufficient.

Method used

The heat conducting sheets containing graphite particles and low melting point metal components are adopted. The graphite particles are oriented in the thickness direction of the thermal layer, and the low melting point metal components are distributed on the surface or inside of the thermal layer. The gap between the thermal conducting sheet and the bonded body is melted and filled to reduce the contact heat. Obstacle.

Benefits of technology

It significantly reduces the thermal resistance of the heat conductor sheet, improves thermal conductivity and adhesion, and adapts to the needs of high-density heating in semiconductor packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119137735A_ABST
    Figure CN119137735A_ABST
Patent Text Reader

Abstract

A thermally conductive sheet provided with a thermally conductive layer containing at least one type of graphite particles (A) selected from the group consisting of scale-like particles, ellipsoidal particles, and rod-like particles, the direction of the scale-like particles being oriented in the thickness direction of the thermally conductive layer, the long axis direction is oriented in the thickness direction of the heat-conducting layer when the particles are ellipsoidal particles, and the long axis direction is oriented in the thickness direction of the heat-conducting layer when the particles are rod-shaped particles, and the heat-conducting sheet contains a metal component having a melting point of 200 DEG C or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a heat conducting sheet, a heat dissipation device and a method for manufacturing the heat conducting sheet. Background Art

[0002] In recent years, the increased density of wiring and electronic components in semiconductor packages using multilayer wiring boards has increased heat generation, and the increased heat generation per unit area due to the high integration of semiconductor elements has increased, and it is desired to improve the heat dissipation from the semiconductor package.

[0003] Generally, a heat sink is used that dissipates heat by sandwiching thermal grease or a thermally conductive sheet between a heat generating body such as a semiconductor package and a heat sink such as aluminum or copper and making them close together. Generally, a thermally conductive sheet is more convenient in terms of workability when assembling a heat sink than thermally conductive grease.

[0004] In recent years, CPU (Central Processing Unit) chips have tended to be larger in area due to multi-core and multi-chip development. In addition, there is a tendency for the crimping pressure between the heat-generating CPU and the heat sink to decrease. Therefore, the thermal conductive sheet is required to be flexible during crimping. In addition, the thermal conductive sheet is required to have excellent thermal conductivity with low thermal resistance even if the thermal conductive sheet becomes thicker due to the height difference of the chip.

[0005] As a thermally conductive sheet, a resin sheet filled with a thermally conductive filler is also known. As a resin sheet with excellent thermal conductivity filled with a thermally conductive filler, a resin sheet in which highly thermally conductive inorganic particles are selected as the thermally conductive filler and the inorganic particles are oriented perpendicularly to the sheet surface has been proposed.

[0006] For example, there are proposed thermally conductive sheets in which a thermally conductive filler (boron nitride) is oriented in a direction substantially perpendicular to the sheet surface (see, for example, Patent Document 1), and thermally conductive sheets in which carbon fibers dispersed in a gel-like substance are oriented perpendicularly to the sheet surface (see, for example, Patent Document 2).

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2002-26202

[0010] Patent Document 2: Japanese Patent Application Publication No. 2001-250894 Summary of the invention

[0011] Technical problem to be solved by the invention

[0012] Patent Documents 1 and 2 study methods for orienting thermally conductive fillers, carbon fibers, etc. in a direction perpendicular to the sheet surface to suppress thermal resistance. In order to cope with the increase in heat generation associated with the high performance and large-scale semiconductors, it is desirable to further reduce the thermal resistance of thermally conductive sheets. Therefore, it is preferred to achieve low thermal resistance based on means other than the orientation of thermally conductive fillers, carbon fibers, etc. contained in the thermally conductive sheet.

[0013] The present disclosure aims to provide a thermally conductive sheet with low thermal resistance, a heat sink having the thermally conductive sheet, and a method for manufacturing the thermally conductive sheet with low thermal resistance.

[0014] Means for solving technical problems

[0015] Specific means for solving the above technical problems include the following.

[0016] <1> A thermally conductive sheet comprising a thermally conductive layer, the thermally conductive layer comprising at least one type of graphite particles (A) selected from the group consisting of flaky particles, ellipsoidal particles, and rod-shaped particles, wherein in the case of the flaky particles, the surface direction is oriented in the thickness direction of the thermally conductive layer, in the case of the ellipsoidal particles, the major axis direction is oriented in the thickness direction of the thermally conductive layer, and in the case of the rod-shaped particles, the major axis direction is oriented in the thickness direction of the thermally conductive layer,

[0017] The thermally conductive sheet includes a metal component having a melting point of 200° C. or less.

[0018] <2> The thermally conductive sheet according to <1>, wherein the metal component is in a particle form.

[0019] <3> The thermally conductive sheet according to <1> or <2>, wherein the metal component is located on at least a portion of a main surface of the thermally conductive layer.

[0020] <4> The thermally conductive sheet according to any one of <1> to <3>, wherein the metal component has a melting point of 60° C. or higher.

[0021] <5> The thermally conductive sheet according to any one of <1> to <4>, wherein the metal component includes at least one element selected from the group consisting of tin, bismuth, indium, zinc, lead, gallium, cadmium, thallium, and antimony.

[0022] <6> The thermally conductive sheet according to any one of <1> to <5>, wherein a mass ratio of the graphite particles (A) to carbon fibers in the thermally conductive layer, that is, graphite particles (A): carbon fibers, is 100:0 to 100:30.

[0023] <7> A thermally conductive sheet comprising a thermally conductive layer, the thermally conductive layer comprising at least one type of graphite particles (A) selected from the group consisting of flaky particles, ellipsoidal particles, and rod-shaped particles, wherein in the case of the flaky particles, the surface direction is oriented in the thickness direction of the thermally conductive layer, in the case of the ellipsoidal particles, the major axis direction is oriented in the thickness direction of the thermally conductive layer, and in the case of the rod-shaped particles, the major axis direction is oriented in the thickness direction of the thermally conductive layer,

[0024] When the thermally conductive sheet is pressed between the heating element and the heat sink, the porosity calculated as the ratio of the area of ​​the gas region to the area of ​​the measurement region on at least one of the interfaces between the heating element and the thermally conductive sheet and between the heat sink and the thermally conductive sheet is 0% to 8%.

[0025] <8> A heat dissipation device comprising a heat generating element, a heat dissipating element, and a thermally conductive sheet according to any one of <1> to <6> disposed between the heat generating element and the heat dissipating element.

[0026] The metal region including the metal component is located on at least a portion of at least one of a main surface of the heat conductive layer located on the heating element side and a main surface located on the heat dissipating element side.

[0027] <9> A heat dissipation device comprising a heat generating element, a heat dissipating element, and a thermally conductive sheet according to any one of <1> to <7> disposed between the heat generating element and the heat dissipating element,

[0028] The porosity calculated as the ratio of the area of ​​the gas region to the area of ​​the measurement region on at least one of the interface between the heating element and the heat conductive sheet and the interface between the heat dissipating element and the heat conductive sheet is 0% to 8%.

[0029] <10> A method for producing a thermally conductive sheet, the method comprising producing the thermally conductive sheet according to any one of <1> to <6>,

[0030] The method for producing the thermally conductive sheet comprises the steps of preparing a composition containing the graphite particles (A) and producing a thermally conductive sheet containing the metal component using the composition.

[0031] <11> The method for producing a thermally conductive sheet according to <10>, wherein the step of producing the thermally conductive sheet includes the steps of forming the thermally conductive layer and attaching the metal component to at least a portion of a surface of the thermally conductive layer.

[0032] <12> The method for producing a thermally conductive sheet according to <10> or <11>, wherein the composition prepared in the step of preparing the composition contains the graphite particles and the metal component.

[0033] Effects of the Invention

[0034] According to the present disclosure, it is possible to provide a thermally conductive sheet having low thermal resistance, a heat sink including the thermally conductive sheet, and a method for manufacturing a thermally conductive sheet capable of manufacturing the thermally conductive sheet having low thermal resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a schematic structural diagram of a thermally conductive sheet according to one embodiment of the present invention, in which a particulate low-melting-point metal component is located on the main surface of a thermally conductive layer.

[0036] Figure 2 This is a schematic structural diagram of a thermally conductive sheet in which a particulate low-melting-point metal component is located inside a thermally conductive layer according to one embodiment of the present invention.

[0037] Figure 3 This is a schematic structural diagram of a heat conductive sheet in which a metal region including a low melting point metal component is located on a main surface of a heat conductive layer according to one embodiment of the present invention.

[0038] Figure 4 A schematic cross-sectional view showing a heat dissipation device in which a heat generating element is a semiconductor chip and a heat dissipating element is a heat sink according to an embodiment of the present invention.

[0039] Figure 5 The diagrams show the states of interfaces obtained by image analysis in Examples 1 to 4 and Comparative Example 1. DETAILED DESCRIPTION

[0040] The following is a detailed description of the embodiments for implementing the present invention. However, the present invention is not limited to the following embodiments. In the following embodiments, unless otherwise specified, the constituent elements (including element steps, etc.) are not essential. The numerical values ​​and their ranges are also the same and do not limit the present invention.

[0041] The term "process" used in the present disclosure includes not only a process that is independent of other processes, but also a process that cannot be clearly distinguished from other processes as long as the purpose of the process can be achieved.

[0042] In the present disclosure, in a numerical range expressed by “to”, the numerical values ​​before and after “to” are included as the minimum value and the maximum value, respectively.

[0043] In the numerical range recorded in the present disclosure, the upper limit or lower limit recorded in one numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other segments. In addition, in the numerical range recorded in the present disclosure, the upper limit or lower limit of the numerical range can also be replaced by the value shown in the embodiment.

[0044] In the present disclosure, each component may include a plurality of substances corresponding thereto. When a plurality of substances corresponding to each component are present in the composition, the content rate or content of each component refers to the total content rate or content of the plurality of substances present in the composition unless otherwise specified.

[0045] In the present disclosure, particles corresponding to each component may contain multiple types. When multiple types of particles corresponding to each component exist in the composition, the particle size of each component refers to the value of the mixture of the multiple types of particles present in the composition unless otherwise specified.

[0046] The term “layer” or “film” used in the present disclosure includes not only a case where the layer or film is formed throughout the entire region when the region where the layer or film exists is observed, but also a case where the layer or film is formed only in a part of the region.

[0047] The term "stacked" in the present disclosure means overlapping layers, and two or more layers may be combined together, or two or more layers may be detachable.

[0048] 〔Thermal Conductive Sheet〕

[0049] The thermally conductive sheet of the present disclosure includes a thermally conductive layer, the thermally conductive layer containing at least one type of graphite particles (A) selected from flaky particles, ellipsoidal particles and rod-shaped particles (also simply referred to as "graphite particles (A)"), in the case of the flaky particles, the surface direction is oriented along the thickness direction of the thermally conductive layer, in the case of the ellipsoidal particles, the major axis direction is oriented along the thickness direction of the thermally conductive layer, and in the case of the rod-shaped particles, the major axis direction is oriented along the thickness direction of the thermally conductive layer, and the thermally conductive sheet contains a metal component with a melting point of 200° C. or less (also referred to as a "low-melting point metal component").

[0050] It is considered that the thermally conductive sheet of the present disclosure has excellent thermal conductivity in the thickness direction and exhibits low thermal resistance because it includes a thermally conductive layer in which the graphite particles (A) are oriented in the thickness direction of the thermally conductive layer.

[0051] Furthermore, it can be considered that the thermally conductive sheet shows lower thermal resistance by containing a low-melting-point metal component. The reason is speculated as follows. It should be noted that the present disclosure is not limited by the following speculation. The thermally conductive sheet in which the graphite particles (A) are oriented along the thickness direction of the thermally conductive layer has unevenness on the surface in contact with the adherend, and most of the thermal resistance comes from the resistance (also referred to as "contact thermal resistance") caused by the gap generated by the contact between the thermally conductive sheet and the adherends such as the heating element and the heat sink in contact with the thermally conductive sheet. The thermally conductive sheet disclosed in the present invention uses a low-melting-point metal component that is a metal component with a relatively low melting point. When the thermally conductive sheet is heated and pressed together with the adherends such as the heating element and the heat sink, the low-melting-point metal component melts due to heat. Furthermore, by applying pressure, the molten low-melting-point metal component is easily present locally at the interface between the thermally conductive sheet and the adherend, and the molten low-melting-point metal component can be used to make the thermally conductive sheet and the adherend fit tightly. At this time, gaps (for example, gaps caused by the irregularities of the thermally conductive sheet) generated when the thermally conductive sheet and the adherend are heat-compressed are filled with the molten low-melting-point metal component, thereby significantly reducing the contact thermal resistance.

[0052] Contact thermal resistance is also likely to occur when there are irregularities on the surface of the adherend, such as a heating element or a heat sink. In this case, it is difficult to reduce the thermal resistance by adjusting the orientation of the thermally conductive filler contained in the thermally conductive sheet. On the other hand, by using the thermally conductive sheet disclosed herein, the thermally conductive sheet and the adherend with irregularities on the surface can be closely fitted by means of the low-melting-point metal component that melts due to heating. At this time, the gap generated when the thermally conductive sheet and the adherend are heated and pressed (for example, the gap caused by the irregularities of the adherend) is filled with the molten low-melting-point metal component, so the contact thermal resistance is greatly reduced.

[0053] The thermally conductive sheet of the present disclosure contains at least graphite particles (A) and a low melting point metal component, and may contain components described below within a range that exhibits the effects of the present disclosure. Materials used in the thermally conductive sheet of the present disclosure are described below.

[0054] <Graphite particles (A)>

[0055] The heat-conducting layer contained in the thermally conductive sheet contains graphite particles (A). It can be considered that the graphite particles (A) mainly play a role as a high thermal conductivity filler. The graphite particles (A) are at least one selected from flaky particles, ellipsoidal particles and rod-shaped particles. In addition, the graphite particles (A) are oriented in the thickness direction of the heat-conducting layer in the face direction in the case of flaky particles, oriented in the thickness direction of the heat-conducting layer in the case of ellipsoidal particles, and oriented in the thickness direction of the heat-conducting layer in the case of rod-shaped particles. In addition, it is preferred that the six-membered ring plane in the graphite particle (A) crystal is oriented in the face direction in the case of flaky particles, oriented in the long axis direction in the case of ellipsoidal particles, and oriented in the long axis direction in the case of rod-shaped particles. The six-membered ring plane refers to the face of the six-membered ring formed in the hexagonal crystal system, that is, the (0001) crystal plane.

[0056] The shape of the graphite particles (A) is more preferably flaky. The selection of flaky graphite particles tends to further improve thermal conductivity. This is believed to be because, for example, flaky graphite particles are more easily oriented in a predetermined direction in the thermal conductive layer.

[0057] Whether the six-membered ring planes in the crystal of the graphite particle (A) are oriented along the plane direction of the flaky particles, the long axis direction of the ellipsoidal particles, or the long axis direction of the rod-shaped particles can be confirmed by X-ray diffraction measurement. Specifically, the orientation direction of the six-membered ring planes in the crystal of the graphite particle (A) is confirmed by the following method.

[0058] First, a sample sheet for measurement is prepared in which the plane direction of the flaky particles of the graphite particles (A), the major axis direction of the ellipsoidal particles, or the major axis direction of the rod-shaped particles are oriented along the plane direction of the sheet. Specific methods for preparing the sample sheet for measurement include, for example, the following methods.

[0059] A mixture of a resin and graphite particles (A) in an amount of 10% by volume or more relative to the resin is formed into a sheet. The "resin" used is not particularly limited as long as it does not show a peak that hinders X-ray diffraction and can be formed into a sheet. Specifically, an amorphous resin having cohesive force as a binder such as acrylic rubber, NBR (acrylonitrile butadiene rubber), and SIBS (styrene-isobutylene-styrene copolymer) can be used.

[0060] The sheet of the mixture is pressed to less than 1 / 10 of the original thickness, and a plurality of the pressed sheets are stacked to form a laminate. The operation of further pressing the laminate to less than 1 / 10 is repeated more than 3 times to obtain a sample sheet for measurement. By this operation, in the sample sheet for measurement, the graphite particles (A) are oriented in the plane direction along the plane direction of the sample sheet for measurement in the case of flaky particles, in the case of ellipsoidal particles, in the state of being oriented in the plane direction of the sample sheet for measurement, and in the case of rod-shaped particles, in the state of being oriented in the plane direction of the sample sheet for measurement.

[0061] The surface of the sample sheet for measurement prepared as described above was subjected to X-ray diffraction measurement. The height H1 of the peak corresponding to the (110) plane of graphite appearing near 2θ = 77° and the height H2 of the peak corresponding to the (002) plane of graphite appearing near 2θ = 27° were measured. The value obtained by dividing H1 by H2 of the sample sheet for measurement prepared in this way was 0 to 0.02.

[0062] Therefore, "the hexagonal ring planes in the crystals of the graphite particles (A) are oriented in the plane direction in the case of flaky particles, in the major axis direction in the case of ellipsoidal particles, and in the major axis direction in the case of rod-shaped particles" means that the surface of a sheet containing graphite particles (A) is measured by X-ray diffraction, and the value obtained by dividing the height of the peak corresponding to the (110) plane of the graphite particles (A) appearing near 2θ=77° by the height of the peak corresponding to the (002) plane of the graphite particles (A) appearing near 2θ=27° is 0 to 0.02.

[0063] In the present disclosure, X-ray diffraction measurement is performed under the following conditions.

[0064] Device: For example, Burker AXS Corporation "D8DISCOVER"

[0065] X-ray source: CuKα with a wavelength of 1.5406nm, 40kV, 40mA

[0066] Step length (measurement of stride width): 0.01°

[0067] Step time: 720 seconds

[0068] Here, “the graphite particles are oriented in the thickness direction of the heat conductive layer in the case of flaky particles, in the thickness direction of the heat conductive layer in the case of ellipsoidal particles, and in the thickness direction of the heat conductive layer in the case of rod-shaped particles” means that in the case of flaky particles, the angle formed by the surface direction and the surface (main surface) of the heat conductive layer (hereinafter also referred to as “orientation angle”) is 60° or more, in the case of ellipsoidal particles, the angle formed by the long axis direction and the surface (main surface) of the heat conductive layer (hereinafter also referred to as “orientation angle”) is 60° or more, and in the case of rod-shaped particles, the angle formed by the long axis direction and the surface (main surface) of the heat conductive layer (hereinafter also referred to as “orientation angle”) is 60° or more. The orientation angle is preferably 80° or more, more preferably 85° or more, and even more preferably 88° or more.

[0069] The orientation angle is an average value obtained by observing a cross section of the heat conductive layer with a SEM (scanning electron microscope) and measuring the angles (orientation angles) formed by the plane direction in the case of flaky particles, the major axis direction in the case of ellipsoidal particles, and the major axis direction in the case of rod-shaped particles and the surface (main surface) of the heat conductive layer for 50 arbitrary graphite particles (A).

[0070] The particle size of the graphite particles (A) is not particularly limited. The average particle size of the graphite particles (A) is preferably more than 1 / 2 of the average thickness of the heat-conducting layer and less than the average thickness in terms of the mass average particle size. If the mass average particle size of the graphite particles (A) is more than 1 / 2 of the average thickness of the heat-conducting layer, an effective heat conduction path can be formed in the heat-conducting layer, and there is a tendency for the thermal conductivity to be improved. If the mass average particle size of the graphite particles (A) is less than the average thickness of the heat-conducting layer, it is possible to suppress the graphite particles (A) from protruding from the surface of the heat-conducting layer, and there is a tendency for the surface of the heat-conducting layer to have excellent adhesion.

[0071] There is no particular limitation on the method for preparing the thermally conductive layer in a manner that the plane direction in the case of flaky particles, the major axis in the case of ellipsoidal particles, and the major axis direction in the case of rod-shaped particles are oriented in the thickness direction, and for example, the method described in Japanese Patent Publication No. 2008-280496 can be used. Specifically, the following method can be used: a sheet is prepared using a composition, the sheets are stacked to prepare a laminate, and the side end surface of the laminate (for example, at an angle of 0° to 30° relative to the normal line from the main surface of the laminate) is sliced ​​(hereinafter also referred to as "laminate slicing method").

[0072] In addition, when the above-mentioned stacking and slicing method is used, the particle size of the graphite particles (A) used as the raw material is preferably 1 / 2 times or more of the average thickness of the thermal conductive layer in terms of mass average particle size, and may also exceed the average thickness. The reason why the particle size of the graphite particles (A) used as the raw material may also exceed the average thickness of the thermal conductive layer is that, for example, even if graphite particles (A) having a particle size exceeding the average thickness of the thermal conductive layer are contained, since the thermal conductive layer is formed by slicing together with the graphite particles (A), the graphite particles (A) will not protrude from the surface of the thermal conductive layer. In addition, when slicing together with the graphite particles (A), a large number of graphite particles (A) that penetrate the thickness direction of the thermal conductive layer are generated, which can form an extremely effective thermal conductive path, and there is a tendency for the thermal conductivity to be further improved.

[0073] When the stacking section method is used, the particle size of the graphite particles (A) used as the raw material is more preferably 1 to 5 times the average thickness of the heat-conducting layer in terms of mass average particle size, and more preferably 2 to 4 times. If the mass average particle size of the graphite particles (A) is more than 1 times the average thickness of the heat-conducting layer, an effective heat-conducting path can be further formed, and the thermal conductivity is further improved. If it is less than 5 times the average thickness of the heat-conducting layer, the area occupied by the graphite particles (A) on the surface portion can be suppressed from becoming too large, and the reduction of adhesion can be suppressed.

[0074] The mass average particle size (D50) of the graphite particles (A) is measured using a laser diffraction particle size distribution device (e.g., Microtrac Series MT3300, manufactured by Nikkiso Co., Ltd.) using a laser diffraction / scattering method, and corresponds to a particle size at which the mass accumulation reaches 50% when a mass cumulative particle size distribution curve is plotted from the smaller particle size side.

[0075] The heat conductive layer may contain graphite particles other than flaky particles, ellipsoidal particles and rod-shaped particles, and may contain spherical graphite particles, artificial graphite particles, exfoliated graphite particles, acid-treated graphite particles, expanded graphite particles, carbon fibers and the like.

[0076] The graphite particles (A) are preferably flaky particles, and flaky expanded graphite particles obtained by pulverizing flaky expanded graphite are preferred because flaky particles having high crystallinity and large particle size can be easily obtained.

[0077] For example, from the viewpoint of the balance between thermal conductivity and adhesion, the content of the graphite particles (A) in the thermal conductive layer is preferably 15 to 50% by volume, more preferably 20 to 45% by volume, and even more preferably 25 to 40% by volume.

[0078] When the content of the graphite particles (A) is 15% by volume or more, thermal conductivity tends to be improved, while when the content of the graphite particles (A) is 50% by volume or less, reduction in pressure-sensitive adhesiveness and adhesion tends to be suppressed.

[0079] Furthermore, when the heat conductive layer contains graphite particles other than flaky particles, ellipsoidal particles, and rod-shaped particles, the content of the entire graphite particles is preferably within the above range.

[0080] The content (volume %) of the graphite particles (A) is a value obtained by the following formula.

[0081] Content of graphite particles (A) (volume %) = [(Aw / Ad) / {(Aw / Ad)+(Xw / Xd)}]×100

[0082] Aw: mass composition of graphite particles (A) (mass %)

[0083] Xw: Mass composition of other optional components (mass %)

[0084] Ad: Density of graphite particles (A) (Calculated with Ad being 2.1 in this disclosure)

[0085] Xd: Density of any other component

[0086] The content of the spherical graphite particles, artificial graphite particles, acid-treated graphite particles or carbon fibers in the thermal conductive layer may be independently 0 to 10% by volume, 0 to 5% by volume or 0 to 1% by volume.

[0087] The mass ratio of graphite particles (A) to carbon fibers in the thermally conductive layer, i.e., graphite particles (A): carbon fibers, may be 100:0 to 100:30, 100:0 to 100:20, or 100:0 to 100:10. Carbon fibers are generally hard, and by making the amount of carbon fibers smaller than that of graphite particles (A), the flexibility of the thermally conductive sheet can be ensured, and an increase in contact thermal resistance tends to be suppressed.

[0088] <Metal Components>

[0089] The thermally conductive sheet of the present disclosure contains a metal component having a melting point of 200° C. or less (low-melting-point metal component).

[0090] In the thermally conductive sheet disclosed herein, the low melting point metal component may be in the form of particles. In this case, the thermally conductive sheet disclosed herein may be a component before being heated and pressed with an adherend such as a heating element or a heat sink. For the thermally conductive sheet after being heated and pressed with an adherend such as a heating element or a heat sink, since the particle-shaped low melting point metal component has undergone a molten state, the low melting point metal component may not be in the form of particles.

[0091] When the low melting point metal component is in the form of particles, the particle size of the low melting point metal component is not particularly limited, and may be 0.5 μm to 60 μm, 1 μm to 30 μm, or 5 μm to 15 μm.

[0092] The particle size (D50) of the low melting point metal component is measured using a laser diffraction particle size distribution device (e.g., "Microtrac Series MT3300" manufactured by Nikkiso Co., Ltd.) using a laser diffraction / scattering method, and corresponds to the particle size at which the mass accumulation reaches 50% when a mass cumulative particle size distribution curve is plotted from the smaller particle size side.

[0093] In the thermally conductive sheet disclosed herein, the configuration of the low melting point metal component is not particularly limited, and it may be configured on the surface of the thermally conductive layer or contained in the thermally conductive layer. In the thermally conductive sheet disclosed herein, from the viewpoint that the gap generated when the thermally conductive sheet and the adherend are heated and pressed is appropriately filled with the molten low melting point metal component, thereby appropriately reducing the contact thermal resistance, it is preferred that the low melting point metal component is located on at least a portion of the main surface of the thermally conductive layer.

[0094] When the low-melting-point metal component is located on at least a portion of the main surface of the thermal conductive layer, the low-melting-point metal component can be configured on the entire main surface, or the low-melting-point metal component can be configured on a portion of the main surface (for example, a portion in contact with an adherend such as a heating element or a heat sink).

[0095] When the low melting point metal component is located on at least a portion of the main surface of the heat conductive layer, the low melting point metal component may be disposed on one main surface or on two main surfaces.

[0096] The melting point of the low melting point metal component is not particularly limited as long as it is 200°C or lower. From the viewpoint of suppressing the melting of the low melting point metal component when the thermal conductive sheet is used for heat dissipation, it is preferably 60°C or higher. From the viewpoint of further appropriately reducing the contact thermal resistance, it is preferably 80°C to 180°C, and more preferably 80°C to 160°C.

[0097] The low melting point metal component is not particularly limited in composition as long as it contains a metal element. The metal element may also contain a non-metallic element that can exhibit the same properties as the metal element. The low melting point metal component preferably contains at least one element selected from tin, bismuth, indium, zinc, lead, gallium, cadmium, thallium, and antimony.

[0098] The low melting point metal component is preferably a low melting point solder having a melting point of 200° C. or less, and more preferably a low melting point lead-free solder having a melting point of 200° C. or less. Specific examples of the low melting point solder include Sn-Bi solder, Sn-In solder, Bi-In solder, Sn-Zn solder, Bi-Sn-In solder, Sn-Zn-Bi solder, and the like.

[0099] For example, from the perspective of the balance between thermal conductivity and adhesion, the content of the low melting point metal component in the thermally conductive sheet is preferably 0.1% to 20% by volume, more preferably 0.5% to 15% by volume, and even more preferably 1% to 10% by volume relative to the total amount of the thermally conductive sheet.

[0100] In the present disclosure, the content of the low melting point metal component contained in the thermally conductive sheet refers to the total content of the low melting point metal component disposed on the surface of the thermally conductive layer and the low melting point metal component contained in the thermally conductive layer.

[0101] <Ingredient (B) that is liquid at 25°C>

[0102] The heat conductive layer contained in the heat conductive sheet of the present disclosure may also contain a component that is liquid at 25°C (hereinafter also referred to as "liquid component (B)"). In the present disclosure, "liquid at 25°C" means a substance that exhibits fluidity and viscosity at 25°C, and the viscosity, which is a measure of viscosity, is 0.0001 Pa·s to 1000 Pa·s at 25°C. "Viscosity" in the present disclosure is defined as the viscosity of a liquid at 25°C using a rheometer at 5.0s -1 Specifically, the "viscosity" is the shear viscosity measured at a temperature of 25°C using a rotational shear viscometer equipped with a cone plate (diameter 40 mm, cone angle 0°).

[0103] The viscosity of the liquid component (B) at 25°C is preferably 0.001 Pa·s to 100 Pa·s, more preferably 0.01 Pa·s to 10 Pa·s.

[0104] The liquid component (B) is not particularly limited as long as it is liquid at 25°C, and is preferably a high molecular compound (polymer). Examples of the liquid component (B) include polybutene, polyisoprene, polysulfide, acrylonitrile rubber, silicone rubber, hydrocarbon resin, terpene resin, acrylic resin, etc. Among them, from the viewpoint of heat resistance, the liquid component (B) preferably contains polybutene. The liquid component (B) may be used alone or in combination of two or more.

[0105] Among them, polybutene refers to a polymer obtained by polymerizing isobutylene or normal butene. It also includes a polymer obtained by copolymerizing isobutylene and normal butene. Structurally, it refers to a polymer having a structural unit represented by "-CH2-C(CH3)2-" or "-CH2-CH(CH2CH3)-". It is sometimes also called polyisobutylene. As long as polybutene contains the above structure, there is no particular limitation on other structures.

[0106] Examples of polybutene include homopolymers of butene and copolymers of butene and other monomer components. Examples of copolymers with other monomer components include copolymers of isobutylene and styrene or copolymers of isobutylene and ethylene. The copolymer may be any of a random copolymer, a block copolymer, and a graft copolymer.

[0107] Examples of polybutene include "NOF Polybutene" produced by NOF Corporation. TMEMAWET (registered trademark)”, “Nisseki Polybutene” of JXTG Nippon Oil & Energy Corporation, “Tetrax” of JXTG Nippon Oil & Energy Corporation, “Himol” of JXTG Nippon Oil & Energy Corporation, and “Polyisobutylene” of Tomoe Industries Co., Ltd.

[0108] It is believed that the liquid component (B) mainly functions as a stress relaxant and a pressure-sensitive adhesive agent having excellent heat resistance and humidity resistance. In addition, the cohesive force and fluidity during heating tend to be further improved by using the hot melt agent (D) described below.

[0109] From the viewpoint of further improving pressure-sensitive adhesive force, adhesion, sheet strength, hydrolysis resistance, etc., the content of the liquid component (B) in the thermally conductive layer is preferably 10% to 55% by volume, more preferably 15% to 50% by volume, and even more preferably 20% to 50% by volume.

[0110] When the content of the liquid component (B) is 10% by volume or more, the pressure-sensitive adhesiveness and adhesion tend to be further improved. When the content of the liquid component (B) is 55% by volume or less, the decrease in sheet strength and thermal conductivity tends to be more effectively suppressed.

[0111] <Acrylate polymer (C)>

[0112] The heat conductive layer included in the heat conductive sheet may further contain an acrylate polymer (C). It is considered that the acrylate polymer (C) mainly functions as a pressure-sensitive adhesive agent and an elasticity-imparting agent for restoring the thickness to follow the warping.

[0113] As the acrylic ester polymer (C), for example, it is preferred to use an acrylic ester polymer (so-called acrylic rubber) obtained by copolymerizing butyl acrylate, ethyl acrylate, acrylonitrile, acrylic acid, glycidyl methacrylate, 2-vinylhexyl acrylate, etc. as main raw material components and methyl acrylate, etc. as needed. The acrylic ester polymer (C) may be used alone or in combination of two or more.

[0114] The weight average molecular weight of the acrylic polymer (C) is preferably 100,000 to 1,000,000, more preferably 250,000 to 700,000, and even more preferably 400,000 to 600,000. A weight average molecular weight of 100,000 or more tends to provide excellent film strength, while a weight average molecular weight of 1,000,000 or less tends to provide excellent flexibility.

[0115] The weight average molecular weight is determined by gel permeation chromatography using a calibration curve of standard polystyrene.

[0116] The glass transition temperature (Tg) of the acrylic polymer (C) is preferably 20° C. or lower, more preferably -70° C. to 0° C., and further preferably -50° C. to -20° C. When the glass transition temperature is 20° C. or lower, the acrylate polymer (C) tends to have excellent flexibility and pressure-sensitive adhesiveness.

[0117] The glass transition temperature (Tg) can be calculated by performing dynamic viscoelasticity measurement by stretching and tan δ derived from the measurement.

[0118] The acrylate polymer (C) may be present in the entire thermal conductive layer by internal addition, or may be locally present on the surface by surface coating or impregnation. In particular, coating or impregnation on one side is preferred because strong adhesion can be imparted only to one side, which is preferred from the perspective of obtaining a sheet with good workability.

[0119] The content of the acrylic ester polymer (C) in the heat conductive layer is preferably 3% to 25% by volume, more preferably 5% to 20% by volume, and even more preferably 7% to 15% by volume.

[0120] <Hot melt (D)>

[0121] The heat conductive layer included in the heat conductive sheet may further contain a hot melt (D). The hot melt (D) has the effect of increasing the strength of the heat conductive layer and improving the fluidity when heated.

[0122] Examples of the hot melt agent (D) include aromatic petroleum resins, terpene phenolic resins, and cyclopentadiene petroleum resins. In addition, the hot melt agent (D) may be a hydrogenated aromatic petroleum resin or a hydrogenated terpene phenolic resin. The hot melt agent (D) may be used alone or in combination of two or more.

[0123] Among them, when polybutene is used as the liquid component (B), the hot melt (D) preferably contains at least one selected from hydrogenated aromatic petroleum resins and hydrogenated terpene phenolic resins. These hot melts (D) have high stability and excellent compatibility with polybutene, and therefore, when constituting the heat conductive layer, there is a tendency to achieve better thermal conductivity, flexibility, and workability.

[0124] Examples of commercially available hydrogenated aromatic petroleum resins include "Arkon" from Arakawa Chemical Industries, Ltd. and "i-marv" from Idemitsu Kosan Co., Ltd. In addition, examples of commercially available hydrogenated terpene phenolic resins include "CLEARON" from Yasuhara Chemical Co., Ltd. In addition, examples of commercially available cyclopentadiene petroleum resins include "Quintone" from Japan Zeon Corporation and "MARUKA LYNCUR" from Maruzen Petrochemical Co., Ltd.

[0125] The hot melt (D) is solid at 25°C, and preferably has a softening temperature of 40°C to 150°C. If a thermoplastic resin is used as the hot melt (D), the softening fluidity during thermocompression bonding is improved, resulting in a tendency to improve adhesion. In addition, if the softening temperature is above 40°C, the cohesive force near room temperature can be maintained, resulting in a tendency to easily obtain the required sheet strength and excellent handling properties. If the softening temperature is below 150°C, the softening fluidity during thermocompression bonding becomes high, resulting in a tendency to improve adhesion. The softening temperature is more preferably 60°C to 120°C. In addition, the softening temperature is measured by the ring and ball method (JIS K2207: 1996).

[0126] From the viewpoint of improving pressure-sensitive adhesive force, adhesion, sheet strength, etc., the content of the hot melt agent (D) in the heat conductive layer is preferably 3 to 25 volume %, more preferably 5 to 20 volume %, and further preferably 5 to 15 volume %.

[0127] When the content of the hot melt agent (D) is 3% by volume or more, pressure-sensitive adhesive strength, heating fluidity, sheet strength, etc. tend to be sufficient, and when it is 25% by volume or less, flexibility tends to be sufficient, resulting in excellent handleability and heat cycle resistance.

[0128] <Antioxidant (E)>

[0129] The heat-conducting layer contained in the thermally conductive sheet may also contain an antioxidant (E) for the purpose of imparting thermal stability at high temperatures. As the antioxidant (E), phenolic antioxidants, phosphorus antioxidants, amine antioxidants, sulfur antioxidants, hydrazine antioxidants, amide antioxidants, etc. may be cited. The antioxidant (E) may be appropriately selected according to the temperature conditions used, and is more preferably a phenolic antioxidant. One antioxidant (E) may be used alone, or two or more may be used in combination.

[0130] Examples of commercially available phenolic antioxidants include ADK STAB AO-50, ADK STAB AO-60, and ADK STAB AO-80 from ADEKA Corporation.

[0131] The content of the antioxidant (E) in the thermal conductive layer is not particularly limited, but is preferably 0.1% to 5% by volume, more preferably 0.2% to 3% by volume, and further preferably 0.3% to 1% by volume. If the content of the antioxidant (E) is 0.1% by volume or more, a sufficient antioxidant effect tends to be obtained. If the content of the antioxidant (E) is 5% by volume or less, a decrease in the strength of the thermal conductive layer tends to be suppressed.

[0132] <Other ingredients>

[0133] According to the purpose, the heat-conducting layer contained in the thermally conductive sheet may also contain other components except graphite particles (A), low melting point metal components, liquid components (B), acrylate polymers (C), hot melts (D), and antioxidants (E). For example, from the viewpoint of flame retardancy, the heat-conducting layer may also contain a flame retardant. The flame retardant is not particularly limited and can be appropriately selected from commonly used flame retardants. For example, red phosphorus flame retardants and phosphate flame retardants can be listed. Among them, from the viewpoint of excellent safety and improving adhesion through plasticizing effect, phosphate flame retardants are preferred.

[0134] As the red phosphorus flame retardant, in addition to using simple red phosphorus particles, various coated red phosphorus flame retardants, masterbatch red phosphorus flame retardants, etc. can also be used for the purpose of improving safety or stability. Specifically, Nobaredo, Nobaclexel, Nobacle, Nobaperet (all trade names) of Phosphorus Chemical Industry Co., Ltd. can be cited.

[0135] As phosphate flame retardants, there can be listed aliphatic phosphates such as trimethyl phosphate, triethyl phosphate, and tributyl phosphate; aromatic phosphates such as triphenyl phosphate, tricresyl phosphate, cresyl diphenyl phosphate, tricresyl phosphate, cresyl di(2,6-xylyl) phosphate, tri(tert-butylphenyl) phosphate, tri(isopropylated phenyl) phosphate, and triaryl phosphate isopropylate; aromatic condensed phosphates such as resorcinol bisdiphenyl phosphate, bisphenol A bis(diphenyl phosphate), and resorcinol bis[di(dimethylphenyl) phosphate], etc.

[0136] Among them, bisphenol A bis(diphenyl phosphate) is preferred from the viewpoint of being excellent in hydrolysis resistance and having an excellent effect of improving adhesion due to a plasticizing effect.

[0137] The content of the flame retardant in the thermal conductive layer is not particularly limited and can be used in an amount that can exert flame retardancy, but is preferably set to about 30 volume % or less. From the viewpoint of suppressing the deterioration of thermal resistance caused by the leakage of the flame retardant component to the surface of the thermal conductive layer, it is preferably set to 20 volume % or less.

[0138] The average thickness of the thermally conductive sheet is not particularly limited and can be appropriately selected according to the purpose. The thickness of the thermally conductive sheet can be appropriately selected according to the specifications of the semiconductor package used. The smaller the thickness, the lower the thermal resistance tends to be, and the larger the thickness, the better the warpage tracking property tends to be. The average thickness of the thermally conductive sheet can be 50μm to 3000μm. From the viewpoint of thermal conductivity and adhesion, it is preferably 100μm to 500μm, and more preferably 100μm to 300μm. The average thickness of the thermally conductive sheet is obtained by randomly measuring the thickness of 3 parts using a micrometer to obtain the arithmetic mean.

[0139] The thermally conductive sheet may have a protective film on at least one surface, preferably on both surfaces, so that the pressure-sensitive adhesive surface of the thermally conductive sheet can be protected.

[0140] The protective film may be, for example, a resin film of polyethylene, polyester, polypropylene, polyethylene terephthalate, polyimide, polyetherimide, polyether naphthalate, methylpentene, etc.; coated paper, coated cloth, and metal foil of aluminum, etc. These protective films may be used alone or in combination of two or more to form a multilayer film. The protective film is preferably surface treated with a silicone-based, silica-based, or other release agent.

[0141] The use of the thermally conductive sheet is not particularly limited. When a semiconductor chip is used as a heating element and a heat sink is used as a heat sink, the thermally conductive sheet disclosed herein is particularly preferably used as a thermally conductive sheet (TIM1; Thermal Interface Material 1) between the semiconductor chip and the heat sink.

[0142] use Figure 1 to Figure 3 Embodiments of the thermally conductive sheet will be described. The thermally conductive sheet of the present disclosure is not limited to the following embodiments.

[0143] Figure 1 In the illustrated thermally conductive sheet 1A, particulate low-melting-point metal component 12A is located on one main surface of thermally conductive layer 11 , and particulate low-melting-point metal component 12C is located on the other main surface of thermally conductive layer 11 .

[0144] Figure 2 In the thermally conductive sheet 1B shown, a particulate low-melting-point metal component 12B is contained in the thermally conductive layer 11 .

[0145] Figure 3 In the illustrated thermally conductive sheet 1 , metal region 13A containing a low melting point metal component is located on one main surface of thermally conductive layer 11 , and metal region 13C containing a particle-shaped low melting point metal component is located on the other main surface of thermally conductive layer 11 .

[0146] (Modification of the thermal conductive sheet)

[0147] A modified example of the thermally conductive sheet disclosed herein comprises a thermally conductive layer, wherein the thermally conductive layer contains at least one graphite particle (A) selected from flaky particles, ellipsoidal particles and rod-shaped particles, wherein in the case of the flaky particles, the surface direction is oriented along the thickness direction of the thermally conductive layer, in the case of the ellipsoidal particles, the major axis direction is oriented along the thickness direction of the thermally conductive layer, and in the case of the rod-shaped particles, the major axis direction is oriented along the thickness direction of the thermally conductive layer, and when the thermally conductive sheet is press-bonded between a heating element and a heat sink, at least one of an interface between the heating element and the thermally conductive sheet and an interface between the heat sink and the thermally conductive sheet has a porosity of 0% to 8% calculated as a ratio of an area of ​​a gas region to an area of ​​a measurement region.

[0148] When the thermally conductive sheet is pressed between the heating element and the heat sink, for example, as a heat sink described later, the porosity is 0% to 8%. Thus, the gaps generated when the thermally conductive sheet and the heating element or the heat sink are pressed together by heating (for example, the gaps from the unevenness of the thermally conductive sheet and the gaps from the unevenness of the heating element or the heat sink) are filled with the molten low-melting-point metal component, thereby significantly reducing the contact thermal resistance.

[0149] From the viewpoint of further reducing the contact thermal resistance, the porosity is preferably 0% to 6%, more preferably 0% to 4%.

[0150] In the present disclosure, the porosity of the interface can be calculated as follows. First, an ultrasonic imaging diagnostic device (e.g., Insight-300, Insight KK) is used to observe the adhesion state of the interface by reflection method at 35 MHz. The ratio of the area of ​​the gas region without adhesion is calculated, and the porosity of the interface can be calculated based on the following formula.

[0151] Interface porosity (%) = 100 × (area of ​​gas region / area of ​​measurement region)

[0152] The modified examples of the thermally conductive sheet of the present disclosure may be appropriately combined with the aforementioned thermally conductive sheet of the present disclosure and its preferred embodiments. For example, the thermally conductive sheet of the modified example may further contain a metal component having a melting point of 200° C. or less.

[0153] [Method for manufacturing thermal conductive sheet]

[0154] The method for producing the thermally conductive sheet is not particularly limited as long as it is a method that can produce a thermally conductive sheet having the above-mentioned structure. Examples of the method for producing the thermally conductive sheet include the following methods.

[0155] In one embodiment, a method for producing a thermally conductive sheet comprises: a step of preparing a composition containing graphite particles (A) and any other components (also referred to as a "preparation step"); and a step of using the composition to produce a thermally conductive sheet containing a low-melting-point metal component (also referred to as a "production step").

[0156] There are no particular limitations on the method for making the thermally conductive sheet contain a low melting point metal component, and examples thereof include method 1 in which the low melting point metal component is mixed with graphite particles (A) when preparing the composition, and method 2 in which the low melting point metal component is attached to at least a portion of the surface of the thermally conductive layer after the thermally conductive layer is formed.

[0157] As method 1, for example, the composition prepared in the aforementioned preparation step may contain graphite particles (A), a low melting point metal component, and any other components. The composition may be prepared by mixing graphite particles (A), a low melting point metal component, and any other components. In method 1, the step of making the thermally conductive sheet may include a step of forming the above-mentioned thermally conductive layer (also referred to as a "forming step").

[0158] As method 2, for example, the process of making a thermally conductive sheet may include a process of forming the above-mentioned thermally conductive layer (also referred to as a "forming process"), and a process of making a low-melting-point metal component adhere to at least a portion of the surface of the above-mentioned thermally conductive layer (also referred to as an "attaching process").

[0159] The forming steps in Method 1 and Method 2 preferably include a step of sheeting the composition prepared in the preparation step to obtain a sheet (also referred to as a "sheet making step"), a step of making a stack of the sheets (also referred to as a "stack making step"), and a step of slicing the side end surfaces of the stack (also referred to as a "slicing step").

[0160] In method 1, a thermally conductive sheet containing a low melting point metal component is obtained through the above-mentioned slicing step. If necessary, after obtaining the thermally conductive sheet containing a low melting point metal component, the low melting point metal component can be attached to at least a portion of the surface of the above-mentioned thermally conductive layer (that is, method 1 and method 2 can be used in combination).

[0161] In method 2, it is preferred to carry out a step of attaching a low melting point metal component to at least a portion of the surface of the thermally conductive layer obtained by the slicing step (also referred to as an "attachment step"). By carrying out the attachment step, a thermally conductive sheet containing a low melting point metal component can be manufactured.

[0162] The method for producing a thermally conductive sheet may further include a step of attaching and laminating the sliced ​​sheet obtained in the slicing step (a thermally conductive sheet containing a low melting point metal component in the case of an attaching step) on a protective film (also referred to as a "laminating step").

[0163] By manufacturing a thermally conductive sheet using this method, an efficient thermal conduction path can be easily formed, so there is a tendency that a thermally conductive sheet having high thermal conductivity and excellent adhesion can be obtained.

[0164] <Preparation process>

[0165] In the preparation step, a composition containing graphite particles (A) and any other components (e.g., a low melting point metal component, a component (B) that is liquid at 25° C., an acrylate polymer (C), a hot melt agent (D), an antioxidant (E), and other components) is prepared. As a method for mixing the components, any method can be used without particular limitation as long as the components can be uniformly mixed. In addition, the composition can also be prepared by purchasing commercially available substances. For details of the preparation of the composition, reference can be made to paragraph

[0033] of Japanese Patent Publication No. 2008-280496.

[0166] <Sheet production process>

[0167] The sheet making process can be carried out by any method without particular limitation as long as the composition obtained in the previous process can be sheeted. For example, it is preferably implemented by at least one forming method selected from rolling, pressing, extrusion, and coating. The details of the sheet making process can refer to paragraph

[0034] of Japanese Patent Publication No. 2008-280496.

[0168] <Laminate production process>

[0169] The laminate production step forms a laminate of the sheets obtained in the previous steps. The laminate can be produced, for example, by stacking a plurality of independent sheets in sequence, or by folding a single sheet, or by rolling a single sheet. For details of the laminate production step, reference can be made to paragraphs

[0035] to

[0037] of Japanese Patent Application Publication No. 2008-280496.

[0170] <Slicing process>

[0171] The slicing step may be any method as long as the side end surface of the laminate obtained in the previous step can be sliced, and there is no particular limitation. From the viewpoint of forming an extremely effective heat conduction path using the graphite particles (A) that penetrate the thickness direction of the heat conductive layer and further improving the thermal conductivity, it is preferred to slice at a thickness of less than 2 times the mass average particle size of the graphite particles (A). For details of the slicing step, reference can be made to paragraph

[0038] of Japanese Patent Publication No. 2008-280496.

[0172] <Attachment process>

[0173] The attachment step may be any method as long as the low melting point metal component is attached to at least a portion of the surface of the thermal conductive layer obtained in the slicing step, and is not particularly limited. For example, metal particles having a melting point of 200° C. or less may be sprinkled on at least a portion of the surface of the thermal conductive layer, or the low melting point metal component may be attached by coating, vapor deposition, sputtering, or the like.

[0174] <Lamination process>

[0175] The lamination step may be any method as long as the sliced ​​sheet obtained in the slicing step (a thermally conductive sheet containing a low melting point metal component in the case of an attachment step) is attached to the protective film, and is not particularly limited.

[0176] 〔Heat dissipation device〕

[0177] The heat dissipation device disclosed in the present invention is a device having a heating element, a heat sink, and a heat conductive sheet of the present invention disposed between the heating element and the heat sink, wherein a metal region containing a low melting point metal component is located on at least a portion of at least one of the main surfaces of the heat conductive layer located on the heating element side and the main surface located on the heat sink side. Preferably, the metal region is located on at least a portion of the main surface located on the heating element side and on at least a portion of the main surface located on the heat sink side, respectively. More preferably, the metal region is located on a region of the main surface located on the heating element side facing the heating element and a region of the main surface located on the heat sink side facing the heat sink, respectively.

[0178] The metal region containing the low melting point metal component may be in a layered form or may be dispersed on the main surface of the thermally conductive sheet. The metal region may be located on at least a portion of the main surface of the thermally conductive sheet, and may be further contained inside the thermally conductive sheet.

[0179] Examples of the heat generating body include semiconductor chips, semiconductor packages, power modules, etc. Examples of the heat dissipating body include radiators, heat sinks, water cooling pipes, etc.

[0180] From the perspective of reducing contact thermal resistance and thermal conductivity, the maximum thickness of the metal region can be 3μm to 20μm on a single side, or 5μm to 15μm. By setting the maximum thickness to 20μm or less, the increase in bulk thermal resistance corresponding to the thermal conductivity of the metal itself can be suppressed. By setting the maximum thickness to 3μm or more, the gap generated when the thermal conductive sheet and the adherend are heated and pressed can be fully filled, and the contact thermal resistance tends to be further appropriately reduced.

[0181] The maximum thickness of the heat conductive layer and the maximum thickness of the metal region can be measured by observing the cross section of the measurement object using an electron microscope. Alternatively, the maximum thickness of the heat conductive layer can be measured using a micrometer, or the maximum thickness of the heat conductive layer and the maximum thickness of a heat conductive sheet having a metal region can be measured, and the maximum thickness of the metal region can be measured by subtracting the maximum thickness of the heat conductive layer from the maximum thickness of the heat conductive sheet.

[0182] Below, use Figure 4 An example of a heat dissipation device is described in more detail. A heat dissipation device using a semiconductor chip as a heating element and a heat sink as a heat sink is described. A semiconductor chip and a heat sink are examples of a heating element and a heat sink, respectively, and the present disclosure is not limited to them. One surface of a thermal conductive sheet 1 is made to fit tightly with a semiconductor chip 2, and the other surface of the thermal conductive sheet 1 is made to fit tightly with a heat sink 3 (heat sink). The semiconductor chip 2 is fixed to a substrate 4 using an underfill 5, and the heat sink 3 is fixed to the substrate 4 using a sealing material 6, and the fit between the thermal conductive sheet 1 and the semiconductor chip 2 and the heat sink 3 is improved by pressing. In addition, it is not necessary that there is one thermal conductive sheet 1, one heating element, and one heat sink. For example, a plurality of semiconductor chips 2 may be provided for a single thermal conductive sheet 1, one semiconductor chip 2 may be provided for a plurality of thermal conductive sheets 1, or a plurality of semiconductor chips 2 may be provided for a plurality of thermal conductive sheets 1. The metal region containing a low melting point metal component is located on the main surface of the thermal conductive sheet 1 on the semiconductor chip 2 side and on the main surface of the thermal conductive sheet 1 on the heat sink 3 side. For example, it may be as follows Figure 3As shown in the thermally conductive sheet 1, metal regions 13A and 13C are respectively located on the main surface of the thermally conductive sheet 1 on the semiconductor chip 2 side and the main surface of the thermally conductive sheet 1 on the heat sink 3 side. Furthermore, metal region 13A may be in contact with heat sink 3, and metal region 13C may be in contact with semiconductor chip 2.

[0183] The heat sink is formed by disposing the heat conductive sheet of the present disclosure between the heating element and the heat sink. By stacking the heating element and the heat sink with the heat conductive sheet interposed therebetween, the heat generated by the heating element can be effectively transferred to the heat sink. By effectively conducting heat, a heat sink can be provided that has a longer service life and functions stably even in long-term use.

[0184] The temperature range in which the thermally conductive sheet can be particularly suitably used may be, for example, -40°C to 150°C, -10°C to 100°C, or -10°C to 80°C. Therefore, as the heat generating element, for example, semiconductor packages, displays, LEDs, electric lights, automotive power modules, and industrial power modules can be cited as examples of preferred heat generating elements.

[0185] Examples of heat sinks include heat sinks using aluminum or copper fins, plates, etc., aluminum or copper blocks connected to heat pipes, aluminum or copper blocks that circulate cooling liquid inside using a pump, and Peltier elements and aluminum or copper blocks having the same.

[0186] The heat sink is formed by bringing the surfaces of the heat conductive sheet into contact with the heating element and the heat sink. There are no particular limitations on the method of bringing the heating element into contact with one surface of the heat conductive sheet and the method of bringing the heat sink into contact with the other surface of the heat conductive sheet as long as they can be fixed in a sufficiently close state.

[0187] For example, a heat conducting sheet is arranged between the heating element and the heat sink, and is fixed by a clamp that can be pressurized to about 0.05MPa to 1MPa, and the heating element is heated in this state, or a method of heating to about 80°C to 200°C (for example, a temperature above the melting point of the low-melting-point metal component) by using an oven or the like can be cited. In addition, a method of using a pressing machine that can be heated and pressurized at 80°C to 200°C and 0.05MPa to 1MPa can be cited. In this method, the preferred pressure range is 0.10MPa to 1MPa, and the preferred temperature range is 100°C to 180°C. By setting the pressure to more than 0.10MPa or the heating temperature to more than 100°C, there is a tendency to obtain excellent adhesion. In addition, by making the pressure less than 1MPa or the heating temperature less than 180°C, there is a tendency to further improve the reliability of the close fit. It can be considered that this is because the heat conducting sheet can be prevented from being excessively compressed and thinning the thickness, or the strain or residual stress of the surrounding parts can be prevented from becoming too large.

[0188] The heat conductive sheet disposed between the heating element and the heat dissipating element is not particularly limited as long as it is the above-mentioned heat conductive sheet. Figure 1 to Figure 3 The heat conductive sheet shown is arranged between the heating element and the heat dissipating element.

[0189] use Figure 1 In the case of the heat conductive sheet 1A shown, the low melting point metal components 12A and 12C on the main surface of the heat conductive sheet 1A are melted by heating and pressing the heat conductive sheet 1A between the heat generating body and the heat sink. The gap generated when the heat conductive sheet 1A is heat-pressed to the heat generating body and the heat sink is filled with the melted low melting point metal component (equivalent to the metal area). As a result, the gap between the heat conductive sheet and the heat generating body or the heat sink is reduced, thereby greatly reducing the contact thermal resistance.

[0190] use Figure 2 In the case of the heat conductive sheet 1B shown, by heating and pressurizing the heat conductive sheet 1B between the heating element and the heat sink, the low melting point metal component 12B contained in the heat conductive sheet 1B melts and easily seeps out to the surface of the heat conductive sheet 1B. As a result, the gap generated when the heat conductive sheet 1B is heated and pressed against the heating element and the heat sink is filled with the melted and seeped low melting point metal component (equivalent to the metal area). As a result, the gap between the heat conductive sheet and the heating element or the heat sink is reduced, thereby greatly reducing the contact thermal resistance.

[0191] As mentioned above, by using Figure 1 as well as Figure 2 The heat conducting sheets 1A and 1B shown in the figure are used to manufacture a heat dissipation device. In the gap between the heat conducting sheet and the heating element or the heat dissipation element, the particle-shaped low-melting-point metal component melts. As a result, the gap is filled with a metal region derived from the low-melting-point metal component, so that the contact thermal resistance can be greatly reduced. Figure 1 as well as Figure 2 When the heat conducting sheets 1A and 1B shown in the figure are used to manufacture a heat dissipation device, the heat conducting sheet contained in the heat dissipation device has the following form: Figure 3 As shown, the heat conductive layer has metal regions derived from a low melting point metal component on two main surfaces, and the metal regions located on the two main surfaces are in surface contact with the heat generating element and the heat dissipating element, respectively.

[0192] use Figure 3 In the case of the heat conductive sheet 1 shown, the metal regions 13A and 13C are melted by heating and pressing the heat conductive sheet 1 between the heat generating body and the heat sink. The gap generated when the heat conductive sheet 1 is heat-pressed to the heat generating body and the heat sink is filled with the melted metal regions 13A and 13C. As a result, the gap between the heat conductive sheet and the heat generating body or the heat sink is reduced, thereby significantly reducing the contact thermal resistance.

[0193] The ratio (compression rate) of the reduced thickness of the thermally conductive sheet after pressure bonding to the initial thickness before being arranged between the heat generating element and the heat dissipating element and pressure bonded may be 1% to 35%.

[0194] Fixation may be performed using a clamp such as a screw or a spring in addition to a clip, and further fixing by a commonly used means such as an adhesive is preferred from the viewpoint of maintaining close contact.

[0195] (Modification of Heat Dissipation Device)

[0196] A modified example of the heat dissipation device disclosed in the present invention comprises a heating element, a heat sink, and a heat conductive sheet of the modified example arranged between the heating element and the heat sink, wherein at least one of the interfaces between the heating element and the heat conductive sheet and the interfaces between the heat sink and the heat conductive sheet, a porosity calculated as a ratio of an area of ​​a gas region to an area of ​​a measurement region is 0% to 8%.

[0197] In the heat dissipation device in which the above-mentioned heat-conducting sheet is arranged between the heating element and the heat sink, the above-mentioned void ratio is 0% to 8%. As a result, the gaps generated when the heat-conducting sheet and the heating element or the heat sink are heat-pressed (for example, the gaps originating from the unevenness of the heat-conducting sheet and the gaps originating from the unevenness of the heating element or the heat sink) are filled with the molten low-melting-point metal component, so that the contact thermal resistance is greatly reduced.

[0198] The modified example of the heat sink of the present disclosure can be appropriately combined with the aforementioned heat sink of the present disclosure and its preferred embodiment. For example, in the heat sink of the modified example, the metal region containing the low melting point metal component can be located on at least a portion of at least one of the main surfaces of the heat conductive layer located on the heating element side and the main surface located on the heat sink side.

[0199] [Example]

[0200] Hereinafter, the present invention will be described in detail by way of examples, but the present invention is not limited to these examples.

[0201] [Example 1 and Example 2]

[0202] The following materials were charged into a kneading mixer (MORIYA MACORPORATION, DS3-SGHM-E type pressurized double-arm kneader) at the mixing ratio (volume %) shown in Table 1 and kneaded at a temperature of 150° C. to obtain a composition.

[0203] <Graphite particles (A)>

[0204] (A)-1: scaly expanded graphite particles (Showa Denko Materials Co., Ltd. "HGF-L", mass average particle size: 270 μm, confirmed by the aforementioned method using X-ray diffraction measurement that the six-membered ring planes in the crystal are oriented along the plane direction of the scaly particles).

[0205] <Liquid component (B)>

[0206] (B)-1: isobutylene-n-butene copolymer (NOF Corporation "NOF Polybutene TM EMAWET (registered trademark), grade 30N)

[0207] (B)-2: Homopolymer of isobutylene ("Tetrax 6T" produced by Nippon Oil Corporation)

[0208] <Acrylate polymer (C)>

[0209] (C)-1: Acrylate copolymer resin (butyl acrylate / ethyl acrylate / acrylonitrile / acrylic acid copolymer, weight average molecular weight: 530,000, Tg = -39°C)

[0210] <Hot melt (D)>

[0211] (D)-1: Hydrogenated petroleum resin (Arakawa Chemical Industries, Ltd. "Arkon P90")

[0212] <Antioxidant (E)>

[0213] (E)-1: Hindered phenol antioxidant (ADK STAB AO-60 from ADEKA Corporation)

[0214] (Fabrication of thermal conductive layer)

[0215] The kneaded composition was placed in an extrusion molding machine (Parker Co., Ltd., trade name: HKS 40-15 extruder), extruded into a flat plate shape with a width of 20 cm and a thickness of 1.5 mm to 1.6 mm to obtain a primary sheet. The primary sheet obtained was pressed and punched with a 40 mm × 150 mm die blade, 61 punched sheets were stacked, and a spacer with a height of 80 mm was clamped in a manner of 80 mm. Pressure was applied to the stacking direction at 90°C for 30 minutes to obtain a 40 mm × 150 mm × 80 mm laminate. Next, the 80 mm × 150 mm side end surface of the laminate was sliced ​​with a woodworking slicer to obtain a thermal conductive layer with a thickness of 0.11 mm.

[0216] (Manufacturing of thermal conductive sheet)

[0217] Solder particles (component Sn-Bi (tin-bismuth alloy), Tin bismuth Alloy Powder (manufactured by 5N Plus Inc.) MCP137 (melting point 137° C.), average particle size: 10 μm) were sprinkled on the two main surfaces of the thermally conductive layer obtained as described above. Thus, a thermally conductive sheet having solder particles attached to the two main surfaces of the thermally conductive layer was obtained. The maximum thickness of the region of the solder particles attached to the thermally conductive sheet is shown in Table 1.

[0218] [Example 3 and Example 4]

[0219] Instead of sprinkling solder particles on the two main surfaces of the thermally conductive layer in Examples 1 and 2, solder particles (component Sn-Bi (tin-bismuth alloy), melting point 137° C.) were added to the composition during the kneading process of the thermally conductive layer to prepare a composition having a mixing ratio (volume %) as shown in Table 1. Kneading, lamination, pressing, and slicing were performed in the same steps as in Examples 1 and 2 to prepare the thermally conductive layer. In Examples 3 and 4, the thermally conductive layer containing solder particles was used as a thermally conductive sheet.

[0220] [Comparative Example 1]

[0221] The materials shown in Table 1 were mixed, laminated, pressed, and sliced ​​in the same steps as Examples 1 to 4 at the mixing ratios (volume %) shown in Table 1 to prepare a thermally conductive layer. In Comparative Example 1, solder particles were not used, and the thermally conductive layer was used as a thermally conductive sheet.

[0222] Table 1

[0223]

[0224] The thermally conductive sheets of Examples 1 to 4 and Comparative Example 1 were evaluated by the following methods. The results are shown in Tables 2 and Figure 5 middle.

[0225] (Determination of thermal resistance)

[0226] Thermal resistance is measured using a desktop xenon flash analyzer (LFA 467Hyper Flash). The thermally conductive sheet of Examples 1 to 4 or Comparative Example 1 punched out into Φ14mm is sandwiched between 1mm copper plates to produce a three-layer structure sample. As sample preparation conditions, the temperature is 150°C and the pressure is 120psi for 3 minutes, and then it is fully cooled at room temperature. In addition, as a pretreatment for the measurement, the copper surface is blackened with carbon spray, and then the measurement is performed. The thermal conductivity λ after removing the influence of the copper plate part from the three-layer structure is obtained. Based on the obtained thermal conductivity λ and thickness t, the thermal conductivity per unit area (1cm 2 ) thermal resistance value X(K·cm2 / W).

[0227] X=(10×t) / λ

[0228] t: Thickness of the thermally conductive sheet of Examples 1 to 4 or Comparative Example 1 (mm)

[0229] λ: Thermal conductivity (W / m·K)

[0230] (Evaluation of interface porosity)

[0231] For the sample of the three-layer structure prepared according to the method described in (Determination of thermal resistance), the porosity of the interface is evaluated as follows. Using an ultrasonic imaging diagnostic device (Insight-300, Insight KK), the adhesion state of the interface is observed by reflection method at 35 MHz, a gain level of 10 dB, and a contrast threshold of 30% to 70%. Furthermore, the image is binarized by image analysis software (Image J) (specifically, 0 to 83 of the histogram is used as the black part and 84 to 255 is used as the white part for black and white), and the ratio of the area of ​​the non-adherent gas area in the area of ​​Φ11 mm (the area of ​​the measurement area) is calculated, and the porosity (%) of the interface is calculated based on the following formula.

[0232] Interface porosity (%) = 100 × (area of ​​gas region / area of ​​measurement region)

[0233] (Thickness Evaluation)

[0234] The maximum thickness of the thermally conductive sheet before compression (the "thickness before compression" in Table 2), the maximum thickness of the metal region before compression (the "thickness of the metal region before compression" in Table 2), and the maximum thickness of the thermally conductive sheet after compression (the "thickness after compression" in Table 2) were measured using a micrometer. The maximum thickness of the metal region before compression was obtained by respectively obtaining the maximum thickness of the thermally conductive layer before compression and the maximum thickness of the thermally conductive sheet before compression, and then subtracting the maximum thickness of the thermally conductive layer before compression from the maximum thickness of the thermally conductive sheet before compression to obtain the maximum thickness of the metal region.

[0235] Table 2

[0236]

[0237] As shown in Examples 1 to 4 and Comparative Example 1, the thermal resistance of the thermally conductive sheet can be reduced by using a low melting point metal component.

[0238] Furthermore, by reducing the porosity of the interface, the thermal resistance of the thermally conductive sheet can be reduced.

[0239] The disclosure of PCT / JP2022 / 028527 is incorporated in its entirety into this specification by reference.

[0240] All documents, patent applications, and technical standards described in this specification are incorporated by reference into this specification to the same extent as if each individual document, patent application, and technical standard was specifically and individually described as being incorporated by reference.

Claims

1. A thermally conductive sheet comprising a thermally conductive layer, the thermally conductive layer comprising at least one graphite particle (A) selected from the group consisting of flaky particles, ellipsoidal particles, and rod-shaped particles, wherein in the case of the flaky particles, the surface direction is oriented along the thickness direction of the thermally conductive layer, in the case of the ellipsoidal particles, the major axis direction is oriented along the thickness direction of the thermally conductive layer, and in the case of the rod-shaped particles, the major axis direction is oriented along the thickness direction of the thermally conductive layer, The thermally conductive sheet includes a metal component having a melting point of 200° C. or less.

2. The thermally conductive sheet according to claim 1, wherein: The metal component is in particle form.

3. The thermally conductive sheet according to claim 1 or claim 2, wherein: The metal component is located on at least a portion of a major surface of the thermally conductive layer.

4. The thermally conductive sheet according to any one of claims 1 to 3, wherein The melting point of the metal component is 60° C. or higher.

5. The thermally conductive sheet according to any one of claims 1 to 4, wherein The metal component includes at least one element selected from the group consisting of tin, bismuth, indium, zinc, lead, gallium, cadmium, thallium, and antimony.

6. The thermally conductive sheet according to any one of claims 1 to 5, wherein The mass ratio of the graphite particles (A) to the carbon fibers in the thermal conductive layer, i.e., graphite particles (A): carbon fibers, is 100:0 to 100:

30.

7. A thermally conductive sheet comprising a thermally conductive layer, the thermally conductive layer comprising at least one graphite particle (A) selected from the group consisting of flaky particles, ellipsoidal particles, and rod-shaped particles, wherein in the case of the flaky particles, the surface direction is oriented along the thickness direction of the thermally conductive layer, in the case of the ellipsoidal particles, the major axis direction is oriented along the thickness direction of the thermally conductive layer, and in the case of the rod-shaped particles, the major axis direction is oriented along the thickness direction of the thermally conductive layer, When the thermally conductive sheet is pressed between the heating element and the heat sink, a porosity calculated as a ratio of an area of ​​a gas region to an area of ​​a measurement region on at least one of an interface between the heating element and the thermally conductive sheet and an interface between the heat sink and the thermally conductive sheet is 0% to 8%.

8. A heat dissipation device comprising a heating element, a heat dissipation element, and a heat conductive sheet according to any one of claims 1 to 6 disposed between the heating element and the heat dissipation element, in, The metal region including the metal component is located on at least a portion of at least one of the main surface of the heat conductive layer located on the heat generating element side and the main surface located on the heat radiating element side.

9. A heat dissipation device comprising a heating element, a heat dissipation element, and a heat conductive sheet according to any one of claims 1 to 7 disposed between the heating element and the heat dissipation element, in, At least one of the interface between the heating element and the heat conductive sheet and the interface between the heat dissipating element and the heat conductive sheet has a porosity calculated as a ratio of an area of ​​a gas region to an area of ​​a measurement region of 0% to 8%.

10. A method for producing a thermally conductive sheet, the method comprising producing the thermally conductive sheet according to any one of claims 1 to 6, The method for producing the thermally conductive sheet comprises the steps of preparing a composition containing the graphite particles (A) and producing a thermally conductive sheet containing the metal component using the composition.

11. The method for manufacturing a thermally conductive sheet according to claim 10, wherein: The step of manufacturing the thermally conductive sheet includes the step of forming the thermally conductive layer and the step of attaching the metal component to at least a portion of the surface of the thermally conductive layer.

12. The method for manufacturing a thermally conductive sheet according to claim 10 or claim 11, wherein: The composition prepared in the step of preparing the composition contains the graphite particles and the metal component.